Pembuatan Sistem Informasi Layanan Pengaduan pada Kelurahan Gandaria Utara Berbasis Website - Yoshua Luwi Setyoadi; Mira Ziveria (UNIVERSITAS KALBIS, 2022)
The complaint system carried out by the people of North Gandaria has so far been carried out in a traditional manner. This study aims to create a public complaints service information system that can be used by using the waterfall system development method. Analysis of the system using fishbone diagrams, cross-functional diagrams. The system design used is Unified Modeling Language (UML), and uses the programming language Hypertext Prepocessor (PHP), Hypertext Markup Language (HTML). And the database uses MySQL, the test carried out is a black box test that produces an online service information system that can be used easily, quickly and can also be used anywhere.